Association between inflammation indicators (MLR, NLR, SII, SIRI, and AISI) and erectile dysfunction in US adults: NHANES 2001-2004 - Heng Liu; Huqiang Dong; Mixue Guo; Hongping Cheng (BMC, 2024)
Abstract Background This study aimed to assess the relationship between multiple indicators of inflammation and erectile dysfunction through an analysis of data from the National Health and Nutrition Examination Survey (NHANES). This represents the first large-scale, cross-sectional investigation that explores this association by jointly analyzing various inflammatory markers. Methods We performed a cross-sectional analysis with NHANES data from 2001 to 2004. Erectile dysfunction (ED) was evaluated through a self-reported questionnaire and testosterone levels, while inflammatory markers were derived from standard blood test parameters. Our approach included multivariate logistic regression, subgroup analyses, generalized additive modeling (GAM), and smoothed curve fitting to evaluate the link between inflammatory markers (NLR, MLR, SII, SIRI, AISI) and ED. Additionally, we utilized receiver operating characteristic (ROC) curves to determine the diagnostic utility of these markers, comparing their area under the curve (AUC) values. Results A total of 3610 participants were included in this study, and the population-weighted ED patients were 18.91%. In the adjusted model, multiple logistic regression analysis showed a positive association between five inflammatory indicators (Ln-NLR, Ln-MLR, Ln-SII, Ln-SIRI, and Ln-AISI) and ED. Smoothed curve fitting showed a nonlinear positive correlation between the five inflammatory indicators and ED. Furthermore, subgroup analyses showed that this correlation was stronger in people older than 50 year. ROC curve analysis showed the highest diagnostic performance for the study outcome with MLR (AUC = 0.616, 95% CI: 0.5952-0.637), which was significantly better than SIRI, NLR, AISI, and SII. Conclusion MLR is potentially more effective than other biomarkers (NLR, SIRI, AISI, SII) in predicting ED. Men with elevated MLR levels should be particularly aware of their increased risk of developing ED.